PENGARUH LAMA FERMENTASI TERHADAP SIFAT FISIK DARI BIJI KAKAO (THEOBROMA CACAO L) KLON SULAWESI SATU (S1) DAN KLON SULAWESI DUA - Rahman, Hidayat; Tooy, Dedie; Tuju, Thelma Doortje Jane (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aimed to determine the fermentation duration and analyze the physical properties of fermented cocoa beans using an experimental method, followed by descriptive analysis and presentation in tables. The results showed that fermentation of Sulawesi 1 and Sulawesi 2 clones for 46 days caused shrinkage in dimensions (length, width, thickness) due to water loss and internal structural changes. In Sulawesi 1, bean length decreased from 21.62 mm (day 4) to 21.07 mm (day 6), width from 12.27 mm to 11.29 mm, and thickness from 8.92 mm to 8.37 mm. Sulawesi 2 showed a similar trend with smaller changes. Geometric diameter (DG) tended to decline on days 56, while roundness remained relatively stable (0.310.32). Bulk density varied slightly, showing both increases and decreases depending on bean structure. Bean weight increased with fermentation time, both in Sulawesi 1 (156.16 g → 158.43 g) and Sulawesi 2 (161.25 g → 166.89 g). Angle of repose and angle of friction increased on days 5–6, indicating higher cohesion and surface roughness. Moisture content decreased significantly by day 6 (Sulawesi 1: 7.28% → 6.29%; Sulawesi 2: 7.27% → 6.20%), supporting drying and storage quality. Overall, six days of fermentation was more effective in reducing moisture, stabilizing density, increasing weight and cohesion, and improving bean quality. It is therefore recommended as the optimal duration to produce cocoa beans with stable physical properties suitable for post-fermentation processing.